Policing and collective efficacy: A rapid evidence assessment - Yesberg, Julia Anne (International journal of police science & management, 2021)
Collective efficacy is a neighbourhood social process that has important benefits for crime prevention. Policing is thought to be one antecedent to collective efficacy, but the mechanisms by which police activity and officer behaviour are thought to foster collective efficacy are not well understood. This article presents findings from a rapid evidence assessment conducted to take stock of the empirical research on policing and collective efficacy. Thirty-nine studies were identified and examined. Overall, trust in police was the aspect of policing most consistently associated with collective efficacy. There was also some evidence that community policing activities, such as visibility and community engagement, predicted collective efficacy. Police legitimacy, on the other hand, was relatively unrelated to collective efficacy: a finding which suggests perceptions of police linked to the ‘action’ of individual officers may be more enabling of collective efficacy than perceptions of the policing institution as a whole. Implications and directions for future research are discussed.